THE ROLE OF MATHEMATICS IN ECONOMICS - Abdukhalikova Dilora Tavakkalovna (Web of Journals Publishing, 2024)
Mathematics plays an important role in economics. Mathematics helps in solving several basic problems in economics, such as modeling, statistical analysis, risk assessment, and optimal computing. Such issues are considered in the article.
Keywords: Economics, mathematics, mathematical statistics, macro, micro, model.